2017
DOI: 10.1055/s-0043-101528
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes geplanter außerklinischer und klinischer Low-Risk Geburten in Niedersachsen

Abstract: Internationally, there is debate on the safety of different birth settings inside and outside of hospitals. Low-risk women in Germany can choose where they give birth, and out-of-hospital births are especially necessary in regions lacking infrastructure. To date, national studies are required. We investigated planned out-of-hospital (OH) and hospital births in Lower Saxony, Germany, in 2005. Women with a singleton fetus in the vertex position were included once they reached 34+0 gestational weeks. 1 273 out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Considerations to reduce the transfer rate of one‐third of nulliparae seeking community birth include an assessment of prolonged labor in community settings. Petersen et al 72 found that nulliparae giving birth in the community had significantly longer durations of labor than those giving birth in hospitals, with a median duration of 9.01 h in community vs. 7.38 h in hospitals. Alliman and Phillippi 73 found a similar pattern in their systematic review of birth center births.…”
Section: Discussionmentioning
confidence: 99%
“…Considerations to reduce the transfer rate of one‐third of nulliparae seeking community birth include an assessment of prolonged labor in community settings. Petersen et al 72 found that nulliparae giving birth in the community had significantly longer durations of labor than those giving birth in hospitals, with a median duration of 9.01 h in community vs. 7.38 h in hospitals. Alliman and Phillippi 73 found a similar pattern in their systematic review of birth center births.…”
Section: Discussionmentioning
confidence: 99%